An investigation of Grade 11 Oshindonga teachers' understanding and implementation of the learner-centered approach adopted in Namibia : a case study - Mbangula, Christofina Nalweendo (Rhodes University, Faculty of Education, Department of Education, 2011)
Before the Republic of Namibia achieved independence in 1990, Bantu Education was the prevailing structure used to promote the social, economic, and political ethos of apartheid through a teacher-centered education system. After 1990, Namibia underwent a major restructuring of education. Learner-centered education was introduced as an inclusive and participatory approach to achieve the reform goals. One of the aims was to review the existing Language policy and to promote mother tongue teaching, since it is through language we internalize our experience and construct our own understanding. In other words, our cognitive, emotional and social development is dependent on language. In this case study, the understanding and implementation of a learner-centered approach in Namibia were investigated in order to gain insights about how the participating education officer, responsible for Oshindonga understands and assists teachers to implement this approach. At the same time, this study aimed at investigating Grade 11 teachers"Ÿ understanding and implementation of LCE in their classrooms. The qualitative methodology in this case study used semi-structured interviews, classroom observations and document analysis for data collection. The data revealed that there are a number of misconceptions. In some cases, what teachers say is not what they do. The findings suggest that teachers, while attempting to implement a learner-centered approach, are not confident about its underlying theory, and therefore the degree of implementation depends on how the teachers used their understanding of that theory in their practice within these conceptual constraints. The study highlights particular challenges and problems that hinder the effective implementation of learner-centered education.
Keywords: Student-centered learning -- Namibia; Ndonga language -- Study and teaching -- Namibia; Teachers -- Training of -- Namibia; Educational change -- Namibia; Education -- Namibia